2016
DOI: 10.1111/imm.12588
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous TWEAK is critical for regulating the function of mouse uterine natural killer cells in an immunological model of pregnancy loss

Abstract: SummaryUterine natural killer (uNK) cells are the most abundant lymphocyte population in the feto-maternal interface during early gestation, and uNK cells play a significant role in the establishment and maintenance of pregnancy-related vascularization, as well as in tolerance to the fetus. Tumour necrosis factor-like weak inducer of apoptosis (TWEAK) and its receptor, fibroblast growth factor-inducible molecule (Fn14), are involved in preventing local cytotoxicity and counterbalancing the cytotoxic function o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…In particular, LPS stimulation induced the expression of Fn14 has been previously reported in vitro studies (Chacón et al, 2006; Qi et al, 2016). Similar results were observed in this study, we found that LPS-stimulated piglet have upregulated expression of TLR4 and Fn14 as well as decreased TWEAK expression in small intestine tissue compared to age matched untreated control piglets.…”
Section: Discussionmentioning
confidence: 65%
“…In particular, LPS stimulation induced the expression of Fn14 has been previously reported in vitro studies (Chacón et al, 2006; Qi et al, 2016). Similar results were observed in this study, we found that LPS-stimulated piglet have upregulated expression of TLR4 and Fn14 as well as decreased TWEAK expression in small intestine tissue compared to age matched untreated control piglets.…”
Section: Discussionmentioning
confidence: 65%
“…Furthermore, NK cell impairment to suppress the expansion and activity of Th17 cells, is identified in patients with recurrent spontaneous abortion [129]. Using the lipopolysaccharide-induced mouse abortion model, researchers found that in the uterus, a reduction of a tumor necrosis factor-like weak inducer of apoptosis (TWEAK) in dNK cells and the upregulation of its receptor, may alter the cytotoxicity of dNK cells and, ultimately, result in pregnancy loss [158]. Quite recently, over-activated dNK cells, with an increased expression of angiogenic cytokines, such as VEGF-A and basic fibroblast growth factor, were observed in women with recurrent miscarriage, which suggests the potential relationship between the dysfunction of dNK cells in regulating angiogenesis and recurrent miscarriage [159].…”
Section: Reproductive Failurementioning
confidence: 99%
“…Protein homogenates from goat cells were extracted as previously described (36). Briefly, the cells were lysed for 20 min on ice in ice-cold lysis buffer (Roche).…”
Section: Western Blot Analysismentioning
confidence: 99%